Intermittent fasting, fatty acid metabolism reprogramming, and neuroimmuno microenvironment: mechanisms and application prospects - Zhang, Anren; Wang, Junyu; Zhao, Yinuo; He, Yu; Sun, Nianyi (Frontiers in Nutrition, 2024)
Intermittent fasting (IF) has demonstrated extensive health benefits through the regulation of fatty acid metabolism and modulation of the neuroimmune microenvironment, primarily via the activation of key signaling pathways such as AMP-activated protein kinase (AMPK) and sirtuin 1 (SIRT1). IF not only facilitates fatty acid oxidation and improves metabolic health, but also enhances mitochondrial function, mitigates oxidative stress, promotes autophagy, and inhibits apoptosis and ferroptosis. These mechanisms contribute to its substantial preventive and therapeutic potential in various conditions, including neurodegenerative disorders such as Alzheimer's and Parkinson's diseases, autoimmune diseases, and neurotraumatic conditions. While supportive evidence has been obtained from animal models and preliminary clinical studies, further large-scale, long-term randomized controlled trials are imperative to establish its safety and evaluate its clinical efficacy comprehensively.